ANALISIS PERUBAHAN TUTUPAN LAHAN PADA ZONASI PENGELOLAAN TAMAN NASIONAL BUKIT TIGA PULUH MENGGUNAKAN CITRA LANDSAT - Eva Achmad; Hamzah Hamzah; Albayudi Albayudi; Priambodo Priambodo (Jurnal Hutan Tropis, 2020)
Bukit Tiga Puluh National Park is one of the important Nature Conservation Areasin central Sumatra because it has a variety of protected flora and fauna. The aim of this research was to observe the rate of change of land cover in the period 2002-2016 in Bukit Tiga Puluh National Park. The research used remote sensing methods by utilizing satellite imagery data to generate land cover data. This study used the classification of supervised images, where the image classes are self-defined based on field data in the form of coordinate points marked with GPS. The study found that land cover has changed from 2002-2016, where thearea of primary forest has decreased 5.422,80 hectares or with average rate 387,34 hectares/year, secondary forest had an increase of 103,00 hectares or with average rate of 7.35 hectares / year, open land increased 2,243.13 hectares or at an average rate of 160.22 hectares / year, dryland agriculture increased 1,929.69 hectares with an average rate of 137, 83 hectares / year, dryland farming mixed with shrubs increased 641.32 hectares or with an average rate of 45.80 hectares / year, and shrubs increased 505.66 hectares or with an average rate of 36.11 hectares / year. The results of the classification in the management zone, the core zone is dominated by primary and secondary forests while in the jungle zone there is a closure other than forests such as agriculture, shrubs and open land as much as 0.05%.